Potential of Uwi (Dioscorea alata L.) as Antiosteoporosis in Histopathological Appearance of Rat Bone (Rattus novergicus) - Ismedsyah; Lavinur; Melva Simatupang (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
Estrogen deficiency can be overcome by hormone replacement therapy, but it causes various unwanted effects in the long term. Phytoestrogens meet the criteria for having estrogen-like activity. Sweet potato root (Dioscorea alata L.) as a phytoestrogen was used in this study to anticipate bone loss (osteoporosis) in postmenopausal women. This study aims to determine the potential of uwi in bone density in rats by looking at the decrease in the number of osteoclasts. Laboratory experimental research method with a research design using RAL (Rak Complete) with five treatments and six replications. The results showed that the average number of osteoclasts from the negative control group was 4.67; the positive control of 2.83; by offering uwi extract at a dose of 600 milligrams/200 grams. Rat BB 2.16; presented Uwi extract dose of 800 milligrams/200 grams of rat B.B. as much as 2.83; presented Uwi extract at a dose of 1000 milligrams/200 grams Rat BB 1.0; and 2.5 . false group. This study concludes that Uwi is likely to maintain bone density in rats with osteoporosis by decreasing the number of osteoclasts.